Os retratos dos Coudreau: índios, civilização e miscigenação através das lentes de um casal de visionários que percorreu a Amazônia em busca do “bom selvagem” (1884-1899) - SOUZA FILHO, Durval de (Universidade Federal do Pará, 2013)
Considering the importance of the iconography, mainly the photography, in order to clarify facts about the history of the Amazon, specially those related to life, culture, natureand the history of occupation of the region that belongs to Indian people and traditional populations, I did an accurated examination of photographs produced by Henri and Octavie Coudreau in their expedition for the interior of Pará, when both work for the government of the State, during the period of 1883 to1899. I worked yet on the material produced only by Octavie Coudreau through the period of 1899 until 1903, after her husband death; at this time she was also working for the Amazonas State government. Through attentive and detailed reading of these pictures, besides the examination of other written sources, including the proper travelers stories, I look for to understand what I can affirm as being the biggest paradox of these travelers de la Troisième République française: the belief in the romantic ideal of the “good savage” and the intransigent defense of a civilization and its inexorable march, which, in last instance, would be responsible for the whole destruction of this “first and integral” man. Another secundary objective is also understand what became the Coudreau couple to be attached to an idea – that later became a belief – that would be possible to find in the Amazon Rain Forest the “good savage”. In my research, I intended, moreover, to reflect on if those facts would be really a belief or simply “bait” to attract their readers. Therefore it’s clear, in the stories of the Coudreau couple, two different speeches: a romantic one, that of the good savage, and a laudatory one, regarded to the progress of the region, the defense of the philanthropic colonization of “the primitive” people and the infinite progress of the Man.